Non-government organizations' adoption of knowledge management systems to enhance service delivery of projects in Grahamstown in the Makana region of the Eastern Cape Province, South Africa - Sherif, Nabiha Mohammed (Rhodes University, Faculty of Commerce, Department of Information Systems, 2018)
The object of this research is to enhance the performance of non-government organizations in the Makana region of the Eastern Cape Province of South Africa by the use of knowledge management practices and principles. Non-government organizations face several service delivery challenges that affect their performance. Knowledge management assists in enhancing performance by means of organizational learning. However, the adoption of knowledge management systems has been limited to the profit-making sector. This study includes an evaluation of the contributing factors influencing the adoption of knowledge management and the extent to which non-government organizations use knowledge management to promote organizational learning. An interpretivist, qualitative case study approach was used on five non-government organizations cases from the Makana region of the Eastern Cape Province of South Africa. A suitability profile sampling method was developed to select the non-government organization cases. The participants in the research include non-government organizations' managers, employees and volunteers. Literature was explored to gain a better understanding of the research area. The research was initiated by an open-ended questionnaire to gather data from the participants, followed by a focus group to enrich the interpretation of the findings. The research proposes a framework to facilitate the adoption of knowledge management systems in non-government organizations. The findings of the research are intended to enhance the performance of non-government organizations projects by means of the use of knowledge management systems.
Keywords: Knowledge management; Organizational learning; Non-governmental organizations -- South Africa -- Makhanda; Human services -- South Africa -- Makhanda